EDUCATIONAL SERVICE MARKETING: EDUCATIONAL SERVICE MARKETING - Bozhkova, V.; Prokopenko, Olha (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Nowadays, at the dawn of the ІІІ century marketing has been developed into wide theory, which got in the practice of many economy subjects: commercial and noncommercial, productive and nonproductive. Therefore the last don’t create material values, but no less important values: the necessities in state government, military defense, safety, free of charge medicine, social security, education, freedom of religion are realized, due to which the safe and proper life of the whole society and partial global necessities decision are depend. Thus, the subjects of the educational activity play an important role in the successful development of the society.